Persepsi Kepemimpinan Guru Berbasis Manajemen Sekolah di Mts. Guppi Taipale'leng: Perceptions of Teacher Leadership Based on School Management in Madrasah Tsanawiyah Guppi Taipale'leng - Musyawarah, St.; Berlian, Ulfa; Rosdiana (ISEDU : Islamic Education Journal, 2024)
The aim of this research is to look at perceptions of teacher leadership based on school management at MTs Guppi Taipale'leng, Gowa Regency. This type of research is qualitative with pedagogical, sociological and phenomenological approaches. Based on the research results, it can be concluded that in terms of school management, the role of the school principal cannot be separated from being the spearhead in realizing good school management. Based on the teacher's perception above, the answer includes positive things regarding school management at MTs Guppi Taipale'leng. Teachers at MTs. Guppi Taipale'leng also felt involved in making decisions at the school, thus creating the perception that the teachers there felt involved. Related to school management at MTs. Guppi Taipale'leng is also well-directed and in good condition because of the structure of each component in the school in terms of leadership, support, teacher involvement and school policies. Don't forget the collaboration between teachers and principals at MTs. Guppi Taipale'leng is very well established, which means that school management can be realized well. Teacher perception is also very necessary because this can help the principal in organizing school management. Because in reality, in creating good school management, there must be cooperation between the school principal and the teachers in the school.